2019
DOI: 10.18270/rsb.v9i2.2794
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Camry dynamometer to the Jamar dynamometer for use in healthy Colombian adults

Abstract: Objective: Hand grip strength can provide an objective index of general upper strength, but hand dynamometer has not been validated for use in Colombia. The objective was to determine the interchangeability between Camry electronic and Jamar hydraulic hand grip dynamometers in a population found on the campus of the Universidad Nacional de Colombia and the elderly living in a community. Methods: This was a cross-sectional concordance study on 18-88-year-old males and females. Data regarding their demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Second, the Jamar hydraulic hand dynamometer is the gold standard for measuring HGS, 22 but we used a different digital hand dynamometer. However, a study that compared the Camry and Jamar dynamometers in healthy adults aged 40–59 years showed that the Camry could replace the Jamar dynamometer 23 . Third, we could not examine physical performance, such as 6‐min walk distance, because many participants were too old to safely undergo the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Jamar hydraulic hand dynamometer is the gold standard for measuring HGS, 22 but we used a different digital hand dynamometer. However, a study that compared the Camry and Jamar dynamometers in healthy adults aged 40–59 years showed that the Camry could replace the Jamar dynamometer 23 . Third, we could not examine physical performance, such as 6‐min walk distance, because many participants were too old to safely undergo the test.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study that compared the Camry and Jamar dynamometers in healthy adults aged 40-59 years showed that the Camry could replace the Jamar dynamometer. 23 Third, we could not examine physical performance, such as 6-min walk distance, because many participants were too old to safely undergo the test. And finally, approximately half of the participants (162 of 279) did not agree to the blood test; thus, accuracy might be lacking in this related analysis.…”
Section: Characteristics Of Phase Angle and Mortality Riskmentioning
confidence: 99%
“…There was a nonsignificant mean difference in readings between the two devices, with the Jamar ® results being marginally higher than the Camry results. This could be attributed to the difference in mechanism and shape of the devices and the feedback that each provides (Amaral, Mancini & Novo 2012 ; Díaz Muñoz & Calvera Millán 2019 ). A number of participants reported differences in tactical feedback between the devices.…”
Section: Discussionmentioning
confidence: 99%
“…The Camry Digital Handgrip Dynamometer has occasionally been reported in the literature; however, its validity in different populations remains unclear (Wilkinson et al 2021 ). A recent study conducted on healthy individuals and community-dwelling elderly individuals in Colombia comparing the Camry Digital Handgrip Dynamometer to the Jamar ® found significant concordance and agreement between devices, most notably in those aged 40–49 years (Díaz Muñoz & Calvera Millán 2019 ). To the best of our knowledge, the Camry Digital Handgrip Dynamometer has not been validated in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence with the Camry dynamometer used to measure muscle strength (LinY et al 2021 ; Park et al 2019 ; Mendes et al 2020 ). However, there is scarce evidence that demonstrates that Camry dynamometer is a reliable device in the geriatric population (Muñoz and Millán 2019 ; Huang et al 2022 ), and to our knowledge no previous studies in a preoperative setting.…”
Section: Introductionmentioning
confidence: 88%